Analisis Akad Murabahah Dalam Platform Digital E-Commerce - Miftachul Ulum; Abdul Mun'im (Miftah : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the application of murabahah contracts in e-commerce digital platforms by reviewing their compliance with the principles of fiqh muamalah. The method used is descriptive qualitative with a normative approach, supported by literature studies and content analysis of digital transaction mechanisms applied in Islamic financial systems. The focus of this study is on how digitization affects the validity, procedures, and ethics of implementing murabahah contracts in online transactions. The results show that the implementation of digital murabahah contracts remains valid as long as it fulfills the pillars and conditions of the contract, namely the existence of the parties ('aqidain), the object of sale and purchase (ma'qud 'alayh), and the sighat or statement of ijab-qabul. The digital system allows these elements to be carried out electronically with clear ownership of goods, transparent prices, and agreed profit margins. Digitalization also increases efficiency and accountability, as well as reducing the potential for gharar (uncertainty) and tadlis (fraud